2006
DOI: 10.1002/cm.20150
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI altered at threonine 406 stabilizes actin filaments in vivo

Abstract: Myosin VI is a minus-end directed actin-based molecular motor implicated in uncoated endocytic vesicle transport. Recent kinetic studies have shown that myosin VI displays altered ADP release kinetics under different load conditions allowing myosin VI to serve alternately as a transporter or as an actin tether. We theorized that one potential regulatory event to modulate between these kinetic choices is phosphorylation at a conserved site, threonine 406 (T406) in the myosin VI motor domain. Alterations mimicki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In myosin VI KD cells, the dense perijunctional packing of F-actin was replaced by a looser organization, without any concomitant change in total cellular F-actin levels. Similarly, earlier studies reported that myosin VI can stabilize actin fi lament networks (Noguchi et al, 2006) and potentially fi laments themselves (Naccache and Hasson, 2006), characteristically promoting the dense packing and accumulation of fi laments. For example, during spermatid individualization in Drosophila, myosin VI is necessary to organize the actin cones that separate the syncytial spermatids.…”
Section: Discussionmentioning
confidence: 55%
“…In myosin VI KD cells, the dense perijunctional packing of F-actin was replaced by a looser organization, without any concomitant change in total cellular F-actin levels. Similarly, earlier studies reported that myosin VI can stabilize actin fi lament networks (Noguchi et al, 2006) and potentially fi laments themselves (Naccache and Hasson, 2006), characteristically promoting the dense packing and accumulation of fi laments. For example, during spermatid individualization in Drosophila, myosin VI is necessary to organize the actin cones that separate the syncytial spermatids.…”
Section: Discussionmentioning
confidence: 55%
“…Based on this model it is generally thought that non-muscle Myo2 causes the sliding of actin filaments. Recent experiments demonstrating that Myo6 stabilizes the actin network during spermatid individualization and in cultured cells depending on its phophorylation argue for Myo6 acting as an actin cross-linker [37,98,101]. Myo1e and Myo1f may also contribute to actin nucleation as has been shown for the long-tail myosins 1 in yeast and amoeba in addition to presenting a MyTH2 domain that has the ability to bind actin filaments [71 -73].…”
Section: S Loubøry and E Coudrier Myosins In Secretionmentioning
confidence: 97%
“…Akt-mediated phosphorylation of Myo5a activates the protein and facilitates insulinstimulated GLUT4 vesicle translocation to the cell surface [35]; conversely, phosphorylation of Myo5 by calcium/calmodulin-dependant protein kinase II (CaMKII) results in the release of the motor from the surface of melanosomes [36]. The phosphorylation of Myo6 is a recently raised and not well understood issue, as it was suggested to regulate the ability of the motor to control actin organization by a yet unknown mechanism [37]. Combinations of all these different mechanisms of regulation enable the same myosin to function on different organelles in distinct cellular locations in order to fulfill specific tasks.…”
Section: Mechanochemical Properties and Regulation Of The Myosins Invmentioning
confidence: 98%
“…This has been shown to be essential for individualization and male fertility [63]. As it will be described in more detail in the next section, phosphorylation of the myosin VI motor domain has been shown to enhance actin anchoring and thus, it has been proposed to be the mechanistic switch that coverts myosin VI from a cargo transporter to an actin tether [64]. Other roles of myosin VI that could reflect its membrane-to-actin anchoring function include: a) its role in the assembly of cadherin cell-to-cell contacts in epithelial cells [65], b) its function in opposing the microtubule-based transport of mitochondria along the neuronal axons by anchoring them to actin [66] and c) more recently, its ability to trigger the assembly of F-actin cages around dysfunctional mitochondria, in order to isolate them and prevent their fusion with neighbouring undamaged pools [67].…”
Section: How the Load Upon A Myosin Modulates Its Functionmentioning
confidence: 99%